Sol narae (Sona) is a Drosophila ADAMTS involved in Wg signaling. - Kim, G.W.; Won, J.H.; Lee, O.K.; Lee, S.S.; Han, J.H.; Tsogtbaatar, O.; Nam, S.; Kim, Y.; Cho, K.O. (Scientific reports, 2016)
ADAMTS (a disintegrin and metalloproteases with thrombospondin motif) family consists of secreted proteases, and is shown to cleave extracellular matrix proteins. Their malfunctions result in cancers and disorders in connective tissues. We report here that a Drosophila ADAMTS named Sol narae (Sona) promotes Wnt/Wingless (Wg) signaling. sona loss-of-function mutants are lethal and rare escapers had malformed appendages, indicating that sona is essential for fly development and survival. sona exhibited positive genetic interaction with wntless (wls) that encodes a cargo protein for Wg. Loss of sona decreased the level of extracellular Wg, and also reduced the expression level of Wg effector proteins such as Senseless (Sens), Distalless (Dll) and Vestigial (Vg). Sona and Wg colocalized in Golgi and endosomal vesicles, and were in the same protein complex. Furthermore, co-expression of Wg and Sona generated ectopic wing margin bristles. This study suggests that Sona is involved in Wg signaling by regulating the level of extracellular Wg.